Cosmological hydrodynamical simulations of galaxy clusters: X-ray scaling relations and their evolution - Truong, N. (2018)
We analyse cosmological hydrodynamical simulations of galaxy clusters to study the X-ray scaling relations between total masses and observable quantities such as X-ray luminosity, gas mass, X-ray temperature, and YX. Three sets of simulations are performed with an improved version of the smoothed particle hydrodynamics GADGET-3 code. These consider the following: non-radiative gas, star formation and stellar feedback, and the addition of feedback by active galactic nuclei (AGN).We select clusters with M500 > 1014M⊙E(z)-1, mimicking the typical selection of Sunyaev-Zeldovich samples. This permits to have a mass range large enough to enable robust fitting of the relations even at z ~ 2. The results of the analysis show a general agreement with observations. The values of the slope of the mass-gas mass and mass- temperature relations at z=2 are 10 per cent lowerwith respect to z=0 due to the appliedmass selection, in the former case, and to the effect of early merger in the latter. We investigate the impact of the slope variation on the study of the evolution of the normalization. We conclude that cosmological studies through scaling relations should be limited to the redshift range z = 0-1, where we find that the slope, the scatter, and the covariance matrix of the relations are stable. The scaling between mass and YX is confirmed to be the most robust relation, being almost independent of the gas physics. At higher redshifts, the scaling relations are sensitive to the inclusion of AGNs which influences low-mass systems. The detailed study of these objects will be crucial to evaluate the AGN effect on the ICM.